Magnetic field-induced fabrication of Fe3O4/graphene nanocomposites for enhanced electrode performance in lithium-ion batteries. Issue 86 (1st September 2016) - Wang, Huan; Xie, Jingyi; Follette, Marissa; Back, Tyson C.; Amama, Placidus B.
Abstract : We report a novel magnetic field-induced approach for the fabrication of nanoporous and wrinkled Fe3 O4 /reduced graphene oxide (RGO) anode materials for lithium ion batteries (LIBs). Abstract : We report a novel magnetic field-induced approach for the fabrication of nanoporous and wrinkled Fe3 O4 /reduced graphene oxide (RGO) anode materials for lithium ion batteries (LIBs). The applied magnetic field improves the interfacial contact between the anode and current collector and increases the stacking density of active material. This facilitates the kinetics of Li ions and electrons, electrode durability, and surface area of active material. As a result, at relatively low specific currents (157 mA g −1 ), wrinkled Fe3 O4 /RGO anodes show high reversible specific capacities (up to 903 mA h g −1 at 157 mA g −1 ). At high discharge rate (1.57 A g −1 ), the specific capacity of wrinkled anodes stay at 345 mA h g −1 (with capacity retention of 90%) after 100 discharge/charge cycles compared to the rapid capacity fading associated with smooth or unwrinkled anodes with a specific capacity of 178 mA h g −1 after the same number of cycles. These results demonstrate the benefit of strong magnetic field treatment during fabrication of nanocomposites containing magnetic nanoparticles.